Cattle and Sheep Diseases Diagnosed in the State of Tocantins - Brazil - Oliveira, Mariana Correia; Ramos, Adriano Tony; Cunha, Isabelle Magalhães; Nunes, Guilherme Sousa; Chenard, Marina Galindo; Nogueira, Vivian de Assunção; Caldas, Saulo Andrade; Helavel, Michel Abdalla (Acta Scientiae Veterinariae, 2019)
Background: Knowing the different diseases that affect the herds of a region is a fundamental necessity, because sanity is one of the main factors limiting animal production. Several studies have reported the diseases affecting the animals of various regions of Brazil; however, no such study was carried out in the state of Tocantins so far. Thus, the objective of this work is to report the main diseases diagnosed in cattle and sheep in the central and northern regions of the state of Tocantins, between January 2011 and December 2015. Materials, Methods & Results: The records and reports of the cattle and sheep treated by the clinicians and pathologists of the Ruminants Medical Clinic (SCMR) of the University Veterinary Hospital (HVU), School of Veterinary Medicine and Zootecnia (EMVZ), University Federal of Tocantins (UFT) during the study period were evaluated. The cases were classified into two categories, conclusive and inconclusive; the cases with conclusive diagnosis were classified according to the etiology and the organic systems involved. In the period of five years, 697 cattle and sheep were treated in the SCMR. The diagnoses were made using epidemiological, clinical, and pathological data, and in some cases, using complementary tests. Among the 697 cases reviewed, 692 (99.2%) and 5 (0.8%) cases were diagnosed conclusively and inconclusively, respectively. The most affected system was the digestive system, which accounted for 260 (37.6%) cases; this was followed by the locomotor 130 (18.8%) cases, nervous 56 (8.1%) cases, reproductive 57 (8.2%) cases, urinary 50 (7.2%) cases, skin 16 (2.3%) cases, muscular 11 (2%) cases, respiratory 34 (4,9%) cases, hemolymphopoietic 28 (3,5%) cases, endocrine 24 (3.5%) cases, sense organs 22 (3,2%) cases, and cardiovascular 4 (0.6%) cases. A total of 220 (31.6%) parasitic, 202 (29%) infectious, 106 (15.2%) toxic, 96 (13.8%) nutritional, 52 (7.5%) by physical agents, and 6 (0.8%) congenital/hereditary diseases were identified. Diseases of neoplastic, metabolic, and inconclusive nature represented 15 (2.1%) cases. Discussion: In this study, the most affected organic system was the digestive system. The disturbances of the digestive system in production animals are reported to comprise a group of important diseases, and they are responsible for large economic losses. Parasitic, infectious, and toxic diseases were more frequently diagnosed, a result similar to those of other studies carried out in Brazil. Haemonchosis was the most frequently occurring parasitic disease and occurrence in sheep. The characteristic clinical signs such as submandibular edema and pallor of the mucosa/carcass and the visualization of the abomasal mucosa in adult specimens on necropsy enabled the diagnosis of this disease. The foot injury were the most frequent disease among the others of the infectious order and affected the sheep. Such lesions are characterized by inflammation and ulceration of the skin of the digits, in which numerous bacteria are isolated. The most frequent toxic disorder was botulism in cattle. A prominent source is osteophatic habit, which is associated with phosphorus deficiency. It is known that the etiologic agent can remain viable for up to one year within the fragments of bones and the tissues of dead animals. This a result similar to those of other studies carried out in Brazil. In this work, for the first time, the identification of the main diseases affecting the cattle and sheep of the central and northern regions of the State of Tocantins was carried out, facilitating the establishment of measures for the prevention, treatment, and control of these diseases.